Cutaneous actinomycosis. A case report - Tomasz Wasyłyszyn; Katarzyna Borowska (Our Dermatology Online, 2016)
A 27 year old patient presented a swollen lesion in the right mandibular area. Prior to the visit the patient was diagnosed with acne and was treated for 6 consecutive months with oral limecycline with no positive response. During the visit the cervicofacial actinomycosis was diagnosed and the patient was administered treatment containing oral amoxycilin plus clavulanic acid among others. The skin lesion disappeared within three weeks. The authors discuss this case in spite of diagnostic difficulties of this uncommon condition, especially while differentiating from acne conglobata.